Nitrogen fertigation for nectarines (Prunus persica var nucipersica): Lateral and vertical nutrient acquisition and cropping behavior in rainfed agroecosystem - SINGH, DEEPIKA; SHARMA, SOM DEV; KUMAR, PRAMOD (The Indian Journal of Agricultural Sciences, 2015)
The present investigation was planned and focused with the objective to compare the effect of nitrogen (N) fertigation and conventional soil fertilization on growth and nutrient dynamics for the establishment of Snow Queen nectarines (Prunus persica var. nucipersica). We determined if the frequency of application of fertigation that could modify cropping behavior of the plantations in integrated horticultural based cropping system under rainfed ecosystem. In the experiment, all plants received the same amount of water with sufficient fertilizer N but the treatment included four fertigation frequencies applied weekly intervals of the recommended dose (RD) of N fertilizers over conventional soil fertilization scheduled at 25% (25% RD-N fertigation), 50% (50% RD-N fertigation), 75% (75% RD-N fertigation) and 100% (100% RD-N fertigation) in the Randomized Block Design replicated thrice. The availability of nutrients at root zone of the trees significantly influenced vegetative growth attributes, the uptake of macro- and micronutrient cations and fruit quality characteristics. Given the fact that all treatments applied with adequate and equal amount of fertilizer and water, however, 75% RD-N fertigation frequency had significantly affected cropping behavior and uptake efficiency both vertically as well as horizontally. The N availability steadily increased with increased depth up to 30 cm after that declined in all the distances at fertigation with 75% RD-N. Highest available P and K in soil was confined to 0-15 cm of soil layer under all fertigation levels and decreased with increase in distance from the emitters and soil depth. With regards to exchangeable Ca and Mg, the contents were decreased in the surface soil than in the subsoil. This superior application also recorded improved vertical and horizontal distribution of available macro- and micronutrient cations in soil, leaf nutrient concentration and fruit quality attributes for growth parameters and fruit quality characteristics which in turn saved 25% of the inorganic fertilizers application.